Analisa Zat Additive pada Carbon Black Nerox 600 terhadap Efek Floating dan Flooding dalam PVC Coating - Candra, Ferdika Dwi; Fadhillah, Arief Rizki; Hermawan, Dadang (PROTON, 2023)
Carbon black is currently widely used in the office world and is easy to obtain, one of which is widely used as printer ink, copier toner, reinforcing agent in the use of plastic, paper, and as a building material. So that carbon black is very easy to find on the market. Because of this uniqueness, the purpose of this research is to make carbon black as an alternative material in the rubber reinforcement process by using a type of carbon black obtained from photocopier toner with type nerox 600 combined with the addition of a percentage of BYK9067 additives using floating and flooding methods. BYK9067 additive is often used as a mixture in PVC coating with alkylammonium salt content. By using these additives as a variation of PVC paint, the best improvement was obtained in the addition of additives in the 3% variation obtained from observations and data analysis of the effect of floating and flooding in PVC coating